A Survey on Development and Recent Trends of Renewable Energy Generation from BIPV Systems. Issue 3 (3rd May 2020) - Sarkar, Debayan; Kumar, Anand; Sadhu, Pradip Kumar
ABSTRACT: The electricity demand of the world is growing at a rapid pace. On the other hand, pollution levels due to conventional power generating techniques are drastically increasing and resulting in harmful environmental issues and impacts. As an alternative to this, renewable or clean energy generation from solar photovoltaic's (PV) in large scale grid connected systems is being increasingly encouraged at the present time. One of the emerging trends in solar PV module power generation is building integrated photovoltaic (BIPV) systems. It meets the local load demands of the building or residential systems and can be used as a stand-alone or on-grid connected system. This paper briefs about the development and recent trends related to renewable energy generation from BIPV systems and its maximum power generation techniques. It also describes both the current-voltage ( I-V ) and power-voltage ( P-V ) characteristics of various BIPV products at dissimilar values of solar irradiation. With BIPV, the building or residential components like the roof, an outer wall, window glass, etc., are replaced by PV array module and hence a dual purpose is served with a reduction in the overall cost.